The Effort to Decrease Maternal and Child Mortality Rates through Cultural Transformation - Atik Triratnawati; Rani Ditya Kristianti; Aldo Pandega Putra; Pandu Bagas Setyaji (International Journal of Public Health Science (IJPHS), 2016)
Maternal and infant mortality in Ende is still high, but research related a social science is rare. The cultural aspect and medical factors such as the lack of primary health care services are also play a role. This study aims are to identifying and formulate the local cultural transformation as a way to solve maternal and infant mortality. This ethnographic research was conducted in 2013. The study carried not only interviews, but also observation towards reproductive-age women, heads of family, traditional birth attendants, doctors, midwives, local leaders, adat leaders, pastors and sisters, local government officials, and head of health district at Ende. Data is analysed phenomenologically. The strong belief to adat and local tradition has implication to people’s attitude towards traditional birth attendants. Traditional birth attendants hold superior position in the community. They also have strong influence due to their ability to massage, correctly guess infant’s sex, reposition infant in the womb, and stop bleeding during labor. Maternal and/or infant mortality has nothing to do with traditional birth attendants because local people believe that such case happens as a result of hex or black magic called ru’u. Anemia, bleeding, food taboo, and incorrect diet pattern worsen the overall condition of pregnant women. Cultural transformation is done by alternating TBAs practices in massaging pregnant women. TBAs are encouraged to massage pregnant women’s back instead of stomach since pregnant women often have to deal with low back pain during pregnancy.